The Influence of Brand Ambassadors and Brand Awareness on Interest in Buying Azarine Sunscreen Products in Surabaya - Permana, Gilang; Supriyono; Hariyana, Nanik (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
The competition in the local beauty industry continues to grow, driven by skincare trends—especially sunscreen—and the influence of Korean culture in Indonesia. As a local brand, Azarine uses marketing strategies by appointing Korean celebrity Lee Min Ho as a brand ambassador and enhancing brand awareness to strengthen consumer recognition and increase purchase intention. This study aims to analyze the influence of brand ambassador and brand awareness on the purchase intention of Azarine sunscreen in Surabaya. Using a quantitative approach with purposive sampling, data were collected from 108 respondents through an online questionnaire and analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM) via SmartPLS. The results show that brand ambassador and brand awareness have a positive and significant effect on purchase intention, indicating that the use of public figures and strong brand awareness are key to attracting consumer interest.